Golden berry fruit modulates inflammation in LPS-stimulated RAW 264.7 macrophages and the DSS-induced acute colitis model - Jenny Castro; Guillermo Lopez-Lluch; Juan Carlos Rodríguez; Rocío de la Puerta; Lía Barrios; Rubén Salas; Luis Franco (Journal of Functional Foods)
Physalis peruviana L. (golden berry) fruit is attractive for its many health benefits, associated with the presence of anti-inflammatory and antioxidant compounds. High fruit consumption has been associated with a lower risk of developing chronic non-communicable diseases. This work evaluated the anti-inflammatory potential of ten fruits cultivated in Colombia, determining their capacity to inhibit ⋅NO production in LPS-activated RAW 264.7 macrophages. The most active extracts were evaluated for their effect on the production of IL-1β, IL-6, TNF-α, and PGE2. Golden berry was the most active extract, so its immunomodulatory effect was evaluated in a model of DSS-induced colitis in BALB/c mice. Dietary supplementation with golden berry attenuates the pathological symptoms of colitis. This effect may be associated with the inhibition of neutrophil infiltration and impacts on the production of IL-6, IL-1β, IL-10, TNF-α, and ROS. Our results suggest that consistently consuming golden berries could benefit intestinal inflammation.